Strategi Pengembangan Industri Kreatif Kerajinan Batik Besurek Untuk Meningkatkan Daya Saing Pelaku Industri Kreatif Kerajinan Batik Besurek Di Kota Bengkulu - Helvoni Mahrina; Nina Yulianasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The development of the creative industry in Indonesia is one sector that has an important role in driving economic growth. As is the case in Bengkulu city, one of the creative industries that is developing is Batik Besurek. What strategies can be done by Batik Besurek business actors and the Bengkulu City Government in developing Besurek Batik business in Bengkulu city? The data collection method is interview, while the data analysis method is descriptive and SWOT analysis. An increase in sales from year to year and designs that are continuously innovated are a form of the spirit of the craftsmen to maintain and make the Besurek Batik Creative Industry a source of livelihood for them. Even so, there are still obstacles they face such as the lack of attention from the Bengkulu City Government towards the craftsmen, lack of access to capital, purchasing raw materials from outside the city which takes time in the delivery process, and the lack of appreciation for local products by the people themselves. The conclusion of this study is that entrepreneurs diversify their products and markets. The development of the Besurek Batik Creative Industry is expected to be given more attention by the Government to provide training or access to capital for industry players in developing their industrial businesses in order to be able to compete with similar industrial businesses in other areas.